Synthesis, function, and therapeutic potential of glycosphingolipids - Dong, Liang; Cao, Zhi; Han, Weidong; Wu, Zhiqiang (Frontiers in Immunology, 2025)
Glycosphingolipids (GSLs) constitute the most structurally diverse subgroup of the sphingolipid family and play crucial roles in a wide variety of cellular functions. The expression of GSLs is tightly controlled during development, with each GSL series exhibiting distinct functional roles in adhesion or signaling, depending on cell type. Genetic defects in lysosomal GSL-degrading enzymes result in GSL storage disorders. However, aberrant and increased expression of GSLs has also been observed in various cancer cells, promoting tumor survival and impairing anti-tumor immunity. Additionally, viruses, pathogens, and bacterial toxins have been found to bind to host GSLs. Therefore, inhibiting GSL synthesis could be a potential therapeutic strategy for such infections or cancers. Here, we discuss the synthesis and classification of GSLs and review their role in disease and treatment.